Clinical mechanisms of repetitive transcranial magnetic stimulation in improving constipation in Parkinson’s disease patients through the gut-brain axis - Bo, Qianlan; Li, Yanmin; Wang, Xiayue; Wang, Huijun; Liu, Huimiao (Frontiers in Aging Neuroscience, 2025)
ObjectivesThis study investigates the clinical efficacy of repetitive transcranial magnetic stimulation (rTMS) in alleviating constipation in patients with Parkinson’s disease (PD) via the gut-brain axis.MethodsFifty-eight PD patients with constipation, admitted from May 2023 to December 2024, were randomly assigned to an rTMS treatment group or a sham rTMS control group (29 patients each). Chronic constipation severity was assessed using the Chronic Constipation Severity Score (CSS) before and 14 days after treatment. Additional measures included weekly spontaneous bowel movements (SBM), complete spontaneous bowel movements (CSBM), the Bristol Stool Scale (BSS), and serum levels of gut-brain peptides (5-HT, BDNF, VIP) and cytokines (IL-6, IFN-γ, TNF-α, IL-4, IL-10).ResultsBaseline characteristics, including CSS scores, were similar between groups (P > 0.05). After 14 days, the study group exhibited significantly lower CSS scores compared to the control group (e.g., CSS post-treatment: study group 4.03 ± 1.01 vs. control group 6.23 ± 1.03, P < 0.001). Both groups showed increased SBM and CSBM frequencies; however, the study group demonstrated significantly higher counts (e.g., CSBM post-treatment: study group 4.67 ± 0.04 vs. control group 4.16 ± 0.06, P < 0.001). BSS scores improved in both groups, with the study group achieving significantly higher scores (P < 0.05). Post-treatment, the study group had significantly higher serum 5-HT (P < 0.001) and BDNF (P = 0.001) levels, and lower VIP levels (P = 0.041) compared to the control group. Cytokine analysis revealed significantly lower pro-inflammatory IL-6 (P < 0.001), IFN-γ (P = 0.034), TNF-α (P < 0.001) and higher anti-inflammatory IL-4 (P < 0.001), IL-10 (P < 0.001) levels in the study group, with corresponding Cohen’s d values indicating medium to very large effect sizes.ConclusionRepetitive transcranial magnetic stimulation effectively improves constipation symptoms in PD patients over a 14 days period. These benefits are associated with favorable modulations of gut-brain peptides and cytokine profiles, suggesting a therapeutic mechanism involving the gut-brain axis. However, direct causality and the long-term effects require further investigation.